An Ergonomic Approach in Designing Nuclear Reactor Simulator Console for Local Operator - Setiawan, Muksin Aji; Santoso, Sigit; Suryono, Tulis Jojok; Kiswanta,; Purwaningsih, Anik; Maerani, Restu; Pamungkas, Adhika Enggar; Atmoko, Dian Fitri; Dwiardhika, Dhanu (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2026)
The construction of a Nuclear Power Plant (NPP) using Small Modular Reactor (SMR) technology is an interesting scheme to support Net-Zero Carbon Emission. The SMR design is an advanced generation reactor with high safety and utilization features, especially for the electricity needed and industry. Its modular size can also be applied to remote areas with lower construction costs compared to other types of power plants. Considering the geographical location and territory of Indonesia, which is an archipelagic country, this type of reactor is suitable for application in Indonesia. To ensure the safety and increase in mastery of the technology, it is necessary to create a simulator to support this program. However, specific regulations governing human-machine interactions (HMI) that cover nuclear reactor simulators are not yet available in Indonesia. This research reviews the US regulations regarding the design of reactor main control rooms, offering options for Indonesian operators by considering anthropometric and ergonomic aspects. In conclusion, the research presents a set of recommendations for developing an appropriate simulator based on these factors.